Ultrasound-Guided Versus Landmark-Based Extracorporeal Shock Wave Therapy for Calcific Shoulder Tendinopathy: An Interventional Clinical Trial - Iosif Ilia; Caius Calin Miuta; Gyongyi Osser; Brigitte Osser; Csongor Toth; Manuela Simona Pop; Ramona Nicoleta Suciu; Veronica Huplea; Victor Niculescu; Laura Ioana Bondar (Diagnostics)
Background/Objectives: Calcific tendinopathy of the shoulder is a degenerative condition characterized by calcium deposits within the rotator cuff tendons, particularly the supraspinatus. It is a frequent cause of chronic shoulder pain and functional limitation, adversely affecting quality of life. While conservative treatments such as nonsteroidal anti-inflammatory drugs (NSAIDs), physiotherapy, and corticosteroid injections are commonly used, extracorporeal shock wave therapy (ESWT) has emerged as a promising non-invasive alternative. This interventional clinical trial compared the efficacy of ultrasound-guided versus landmark-based ESWT in treating calcific tendinopathy. Methods: Eighty-four patients with ultrasound-confirmed calcific tendinopathy were randomized into two groups. Group 1 received ultrasound-guided ESWT with real-time targeting of the deposit; Group 2 received landmark-based ESWT based on anatomical palpation. Both groups underwent three sessions (2000 impulses at 2.2 bars, energy level 5, 8 Hz). Clinical outcomes were assessed using the Constant–Murley score (CMS) at baseline, 12 weeks, and 6 months. Calcific deposit resorption was evaluated via ultrasound imaging. Results: The ultrasound-guided group showed a significant improvement in CMS from a median of 50 (range: 30–75) at baseline to 97 (52–100) at 6 months. The landmark-based group also improved, from 48 (32–74) to 79 (40–96). At 6 months post-treatment, 90.9% of patients in the ultrasound-guided group achieved successful outcomes (CMS ≥ 86), compared to 50% in the landmark-based group. Complete calcific resorption occurred in 65.9% of patients in Group 1, compared to 50% in Group 2; 15% of patients in Group 2 showed no resorption. Conclusions: Ultrasound-guided ESWT was significantly more effective than landmark-based ESWT in improving shoulder function, reducing pain, and promoting calcific deposit resorption. These findings support ultrasound guidance as a preferred approach for optimizing ESWT outcomes in patients with calcific tendinopathy of the shoulder.